Folic acid for the primary prevention of stroke: a systematic review and meta-analysis - Yang, Jianjian; Wang, Jia; Li, Bo; Zhang, Yaxi (Frontiers in Nutrition, 2024)
Results from studies were inconsistent with regard to the effect of folic acid on the primary prevention of stroke. The aim of this study was to analyze the association between folic acid and the primary prevention of stroke using the data from observational studies and randomized controlled trials (RCTs).Eligible publications published until June 2024 were searched in the database of PubMed, Web of Science and Embase. This study included all observational studies and RCTs of folic acid with first stroke as the reporting endpoints. Relative risks (RRs) and 95% confidence intervals (CIs) were pooled in the random-effects model to assess the effect of folic acid on the primary prevention of stroke.Results from 12 observational publications with 16 research, including 312,320 participants, were combined to explore the association between dietary folic acid intake and the primary prevention of stroke. The results showed that high dietary folic acid intake was associated with a 17% reduction in stroke incidence (RR:0.83; 95%CI: 0.73-0.94), and the effect of dietary folic acid was greater in areas without grain fortification (RR:0.80; 95%CI: 0.67-0.95). The pooled results from 12 RCTs, totaling 75,042 participants, indicated that folic acid supplementation was not associated with the stroke primary prevention (RR:0.92; 95%CI: 0.80-1.05), but folic acid supplementation was effective in areas without grain fortification (RR:0.78; 95%CI: 0.68-0.89).Our meta-analysis demonstrated that dietary folic acid is effective in stroke primary prevention, and folic acid supplementation is effective in stroke primary prevention only in areas without grain fortification.